2014
DOI: 10.1007/s00787-014-0545-8
|View full text |Cite
|
Sign up to set email alerts
|

Children diagnosed with attention deficit disorder and their hospitalisations: population data linkage study

Abstract: Examine the hospital admission risk in young children who are subsequently diagnosed with attention deficit hyperactivity disorder (ADHD). We conducted a population-based, record linkage study. Records of all non-Aboriginal children under 18 years who met the DSMIV/ICD10 criteria for ADHD and prescribed stimulant medication in Western Australia between 2003 and 2007 (n = 11,902) were linked to two other health data systems-the hospital morbidity data system and the midwives notification system (MNS). The non-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
2
22
2
Order By: Relevance
“…115 Registry-based studies also provide support for increased incidence of ear infections (rg = 0.20 + 0.05, p = 2.0x10 -4 ) and psoriasis (rg = 0.23 + 0.07, p = 1.0x10 -3 ) among individuals with ADHD. 114,[116][117][118] On the other hand, ADHD was positively correlated with CRP (rg = 0.23 + 0.06, p = 2.0x10 -4 ), though a relatively large epidemiological study finds no association in affected individuals. 119 The negative correlation between anorexia nervosa and CRP (rg = -0.30 + 0.08, p = 1.0x10-4) is borne out in a recent meta-analysis of relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…115 Registry-based studies also provide support for increased incidence of ear infections (rg = 0.20 + 0.05, p = 2.0x10 -4 ) and psoriasis (rg = 0.23 + 0.07, p = 1.0x10 -3 ) among individuals with ADHD. 114,[116][117][118] On the other hand, ADHD was positively correlated with CRP (rg = 0.23 + 0.06, p = 2.0x10 -4 ), though a relatively large epidemiological study finds no association in affected individuals. 119 The negative correlation between anorexia nervosa and CRP (rg = -0.30 + 0.08, p = 1.0x10-4) is borne out in a recent meta-analysis of relevant studies.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al. have previously shown that infection‐related hospitalizations, including intestinal infections, bacterial and viral infections, pyrexia of unknown origin, acute respiratory infections, ear and tonsillar infections, were significantly associated with being diagnosed and treated for ADHD (Silva, Colvin, Hagemann, Stanley, & Bower, ). In contrast, we observed that children seropositive to ≥8 polyomaviruses presented less ADHD‐related symptomatology at 4 years of age compared to children seropositive to ≤3 polyomaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research suggests that children with ADHD are at increased risk of overweight/obesity compared with non‐ADHD controls (Chen et al ; Cortese, Moreira‐Maia, St. Fleur et al ; Cortese & Vincenzi ; Erhart et al ; Halfon et al ; Waring & Lapane ; Yang et al ), particularly unmedicated children (Byrd et al ; Cortese et al ; Waring & Lapane ). Sleep problems, including difficulties with initiating and maintaining sleep, are more common in children with ADHD compared with their peers (Cortese et al , Sung et al ), as is the prevalence of serious injuries (Lange et al ; Silva et al ).…”
Section: Introductionmentioning
confidence: 99%